2008
DOI: 10.12702/1984-7033.v08n03a07
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence and parent selection of sugarcane clones

Abstract: -The objective of this study was to estimate the genetic divergence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For many years, plant breeding programs depended on selecting genotypes by analyzing each agronomic variable individually, estimating genetic parameters, applying selection indices for traits and analyzing the environments to check the genotype x environment interaction. In recent years, multivariate methods and mixed models have become more important due to advances in computer software, and are being applied to evaluate genetic divergence (Costa et al, 2006;Oliveira et al, 2008;Bizari et al, 2014), select genotypes and progenies (Vianna et al, 2013;Dallastra et al, 2014), study adaptability and stability of genotypes (Maia et al, 2006;Mendonça et al, 2007;Borges et al, 2010b;Gomez et al, 2014), estimate genotypic values and study genetic parameters (Duarte et al, 2001;Lopes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For many years, plant breeding programs depended on selecting genotypes by analyzing each agronomic variable individually, estimating genetic parameters, applying selection indices for traits and analyzing the environments to check the genotype x environment interaction. In recent years, multivariate methods and mixed models have become more important due to advances in computer software, and are being applied to evaluate genetic divergence (Costa et al, 2006;Oliveira et al, 2008;Bizari et al, 2014), select genotypes and progenies (Vianna et al, 2013;Dallastra et al, 2014), study adaptability and stability of genotypes (Maia et al, 2006;Mendonça et al, 2007;Borges et al, 2010b;Gomez et al, 2014), estimate genotypic values and study genetic parameters (Duarte et al, 2001;Lopes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The number of individuals in each group varied in both the environments. Earlier studies (Silva et al, 2005;Lopes et al, 2008) reported variation in the number of groups and genotypes within each group according to environment. The variability for cane height, cane diameter and single cane weight were found out by PCA.…”
Section: Resultsmentioning
confidence: 99%